2013
DOI: 10.1089/pop.2012.0083
|View full text |Cite
|
Sign up to set email alerts
|

Coalitions for Impacting the Health of a Community: The Summit County, Ohio, Experience

Abstract: Community coalitions have the potential to catalyze important changes in the health and well-being of populations. The authors demonstrate how communities can benefit from a multisector coalition to conduct a community-wide surveillance, coordinate activities, and monitor health and wellness interventions. Data from Summit County, Ohio are presented that illustrate how this approach can be framed and used to impact community health positively across communities nationwide. By jointly sharing the responsibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Much of the literature on rural healthccare focuses on the increasingly urgent crises facing rural communities [30], whereas a majority of the literature on health coalitions addresses strategies outside of rural areas [20]. In examining rural coalitions’ challenges and successes, we uncovered the entrepreneurial strategies that coalitions and rural communities undertook to innovate and adapt with limited resources to improve material conditions and increase access to health services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the literature on rural healthccare focuses on the increasingly urgent crises facing rural communities [30], whereas a majority of the literature on health coalitions addresses strategies outside of rural areas [20]. In examining rural coalitions’ challenges and successes, we uncovered the entrepreneurial strategies that coalitions and rural communities undertook to innovate and adapt with limited resources to improve material conditions and increase access to health services.…”
Section: Resultsmentioning
confidence: 99%
“…However, little research explicitly examines the experiences and strategies of coalitions, with their limited resources and status, in targeting health inequities. The emergence and existence of health coalitions have been implicitly linked to inequitable distribution of health services and resources [20]. The purpose of this study was to understand the entrepreneurial experiences and strategies of rural coalitions to effect change in the delivery of health services for older adult populations within their communities.…”
Section: Introductionmentioning
confidence: 99%
“…There are some early lessons learned from working with coalitions that are important to consider for those interested in using the model. It should be noted, however, that a coalition-based approach is not the only way to apply the empower action model but can be a way to encourage multilevel impact on health and well-being (Janosky et al, 2013). First, we found that a community coach, or facilitator, is key to implementing the model.…”
Section: Discussionmentioning
confidence: 99%
“…Coalitions generally enhance cultural fit and community acceptance of such programming, thereby increasing program effectiveness and participation by disparate population groups (Stith et al, ). Broad‐based coalitions like Know Your Numbers 46041 , can support effective use of limited resources (Janosky et al, ), something particularly important in rural settings where many barriers exist including limited healthcare providers and resources, lack of public transportation options, lack of insurance, etc. The academic‐practice partnership approach used in this study supported the development of a research design which would work for the coalition and program participants.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the process, feedback provided by participants and program staff during program offerings was used to inform and enhance both coalition programming and the research process to best implement and evaluate the initiatives designed to support healthier lifestyle behaviors. Research has indicated that coalitions providing programming in a variety of community‐based settings can result in community and individual level changes for a variety of health behaviors and outcomes (Anderson et al, ; Janosky et al, ). A systematic review by Anderson et al, , also indicated that community coalition‐led interventions may help create connections between disparate populations, health providers, and health resources, ultimately improving health outcomes.…”
Section: Discussionmentioning
confidence: 99%